Implication of Orai1 in the diastolic calcium dysregulation during Ischemia and Reperfusion in cardiomyocytes. (10th June 2022) - Falcon Boyano, D; Mayoral Gonzalez, I; Calderon Sanchez, E; Ordonez, A; Smani, T
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Agencia Estatal de Investigación Background: It is well established that abnormalities in the regulation of the intracellular concentration of Ca2+ ([Ca2+]i) occurrs in diseased heart. Ischemia/Reperfusion (I/R) syndrome is characterized by [Ca2+]i overload that might be associated with the increase of left ventricular pressure, which might trigger diastolic dysfunction. Several studies have demonstrated that Orai1/2/3 isoforms of the Store Operated Calcium Channels (SOCC) and TRPC channels play a role in cardiac pathologies. Previously, we demonstrated that the expression of Orai1 increased after I/R although their role in the diastolic [Ca2+]i regulation is unknown. Objective: The aim of this study was to examine the role of SOCC in the diastolic [Ca2+] after I/R in cardiomyocytes and the activation of transcription factors by I/R. Materials and Methods: The experiments were performed in adult (ARVM) and neonatal rat ventricular cardiomyocytes (NRVM) and in a rat model of myocardial I/R. Ca2+ studies were realized using microfluorimetric technique in FURA-2AM loaded cardiomyocytes. To evoke [Ca2+]i transients, ARVM were field stimulated at 0.5Hz and NRVMs at 1Hz. Immunofluorescence was used to investigated CREB activation using a specific phospho-CREB antibody and protein expression was analysed by Western Blot. Orai1 expression was assessed in rat samples and in ventricular biopsies of patients with ischemic heart failure. Results: We found that field stimulation of ARVM from I/R animal showed significant increase in the diastolic [Ca2+]i as compare to AVRM isolated from sham rats. Also, NRVM subjected to simulated protocol of I/R presented similar increase in the diastolic [Ca2+]i. These responses correlated with significant increase in the expression of Orai1 in both cardiomyocytes. Interestingly, NRVM and ARVM preincubation with SYNTA-66 and GSK-7975A to block SOCC successfully reduced the increase in the diastolic [Ca2+]I induced by IR. Moreover, we found that I/R promoted CREB activation through PKA activation, but not though EPAC2 or ERK1/2. Finally, we found that Orai1 is overexpressed in ventricle biopsies of patient with heart failure from ischemic origin. Conclusions: Our results confirms that I/R induced an upregulation of Orai1 which was associated with diastolic dysfunction, suggesting that Orai1 plays a role in the I/R induced diastolic [Ca2+]i increase. Moreover, our data demonstrated the activation of the transcription factor CREB in cardiomyocytes after I/R, known to activate a plethora of genes involved in the adverse cardiac remodelling.